Healing spaces : the science of place and well-being - Sternberg, Esther M. (Belknap Press of Harvard University Press, 2009)
A respected neuroscientist shows how some surroundings - from hospital rooms with windows to traditional religious shrines - can greatly improve healing from illness, and shows ways to create a healthier environment.